Gestión de políticas internas de crédito del Almacén Tropi Motors - Guerrero Maldonado, Justin Wilfrido (2020)
Tropi Motors is a commercial company that belongs to the Unicomer group, which is dedicated to the sale of motorcycles, currently it has four sellers and the warehouse manager who also carries out sales activities. The present case study is called "Management of internal credit policies of the Topi Motors store" with the purpose of knowing how their internal policies affect, what problems they generate and the inconveniences that arise, among other circumstances that will leave. describing in the development of the case its causes, consequences and how it ends. In addition, the purpose is to know the policies that control the processes and functions that allow reducing the problems that occur in the company, improving financial profitability